THE PURIFICATION OF USED PALM OIL USING BAGASSE AND BANANA "KEPOK" PEELS AS AN ADSORBENT - MULIANI, AKIEN (Jurnal Sains Pertanian Equator, 2019)
The purpose of this research is to know the best ratio based on the combination of the bagasse and banana "kepok" peels to the used palm oil purification. This research used Randomized Block Design one factor, the ratio formula of the combination bagasse and banana "kepok" peels (7 times treatment that is control, 0:100, 20:80, 40:60, 60:40, 80:20, and 100:0, 4 times replication). The data analyzed by ANOVA 5%, if there is significant treatment, then it continued by Turkey"™s (HSD Test). Data from hedonic analyzed by Friedman test. The result showed the combination of bagasse and banana "kepok" peels at ratio 100:0 is the best treatment. The quality of used oil are moisture content 0.35%, FFA 0.96%, relative density 0.956 g/mL, saponification 167.85 mg KOH/g and viscosity 0.56 cps. Organoleptic evaluation best result is colour 1.24 (yellow clear to bit yellow) and smell 1.4 (no rancid to bit rancid).